(untitled) (Journal of Enam Medical College, 2016)
Acid throwing, also called an acid attack or vitriolage, is a form of violent assault. It is defined as the act of throwing strong corrosive on the body of a person with the intention of injuring or disfiguring [them] out of jealousy or revenge. Here we present a case of a 19- year-old girl who was victimized because she refused a love proposal. She was admitted in the One Stop Crisis Center (OCC) of Dhaka Medical College Hospital. Acid burn injuries involved whole of the right side of the face, front and adjacent right side of the neck, right shoulder and front of the right side of the chest. The burnt areas were wet with serous discharge. She was treated with intravenous fluid, antibacterial ointment on her affected area, her wounds were washed with plenty of water and sodium-bi-carbonate, antibacterial eye ointment was applied on her eyes, tetanus toxoid and analgesics were given. J Enam Med Col 2016; 6(1): 47-50